Relationship of the Youth Unemployment and Determinants of the Labour Market in the Balkan Countries - Pavlović, Dejana; Zubović, Jovan; Obradović, Vladimir (Industrija, 2017)
Balkan countries are facing with a large number of unemployed young people. There is no doubt that financial crises have the biggest influence on the youth labour market. The remainder of this paper is presenting the research results showing the correlation between the unemployment rate (among youth and adults) and the determinants of the labour market in order to determine whether there is a difference in the impact of labour market indicators on the unemployment rates by gender and age. The study focuses on 11 Balkan countries in the period from 2008 to 2014. The data were collected from the Fraser Institute research specifically from “The Economic Freedom of the World: 2016 Annual Report”.